2006
DOI: 10.1128/iai.00234-06
|View full text |Cite
|
Sign up to set email alerts
|

Hybridoma Passage In Vitro May Result in Reduced Ability of Antimannan Antibody To Protect against Disseminated Candidiasis

Abstract: We previously reported the enhanced resistance of monoclonal antibodies B6.1 (an immunoglobulin M [IgM]) and C3.1 (an IgG3) against experimental candidiasis. Both MAbs recognize the same fungal epitope. We have since found that a highly passaged B6.1 hybridoma (hp-B6.1) resulted in antibody that has little protective potential. The potential clinical applicability of the antibody and our interest in understanding antibody protection against candidiasis led us to investigate an explanation for this phenomenon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…On closer examination, however, in at least one case, T H 2-derived antibodies have a protective effect by somehow augmenting cell-mediated immunity 39 . In other cases, antibodies can function as opsonins, promoting fungal ingestion and even killing by phagocytes, and several antibodies are directly fungicidal [40][41][42][43][44][45][46][47] (TABLE 1). These kinds of activities are complementary, rather than exclusive, to cell-mediated mechanisms.…”
Section: Evidence For Protective Antibodies Against Fungal Diseasementioning
confidence: 99%
“…On closer examination, however, in at least one case, T H 2-derived antibodies have a protective effect by somehow augmenting cell-mediated immunity 39 . In other cases, antibodies can function as opsonins, promoting fungal ingestion and even killing by phagocytes, and several antibodies are directly fungicidal [40][41][42][43][44][45][46][47] (TABLE 1). These kinds of activities are complementary, rather than exclusive, to cell-mediated mechanisms.…”
Section: Evidence For Protective Antibodies Against Fungal Diseasementioning
confidence: 99%
“…The increase in the number of cell subcultures performed over a time, or cell passages over a time (number of cell passages), could favor the growth of unproductive cell cultures, reduce productivity and reduce the mAb protective potential against infections (Xin and Cutler 2006;Zhu and Yang 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that murine hybridoma strain AB-1432 lost 50 % of mAb productivity when cultured in DMEM supplemented with 10 % (v/v) fetal bovine serum (FBS) as of P20 (Schmid et al 1990). Whereas hybridoma B6.1 cells maintained at high passages reduced the protective capacity of their secreted mAb (Xin and Cutler 2006). The production instability in recombinant mAb in CHO cells can occur through gene silencing mechanism, or else the progressive loss in the number of copies of the recombinant gene, reducing mAb yield as of P14 or P95 (Beckmann et al 2012;Kim et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgE may represent one example, but although a relationship between allergic hypersensitivity and recurrent vaginal candidiasis has been speculated (4), the role in systemic or disseminated mycotic diseases requires more investigation. We showed that certain IgM and IgG 1 antibodies with anti-mannan specificity may not be protective against disseminated candidiasis (5,6), but whether other antibody classes and specificity enhance disease progression is unknown. Nonetheless, in recent years, attention to these various details has resulted in solid evidence for antibody defense against candidiasis and cryptococcosis, and perhaps other mycoses (1).…”
mentioning
confidence: 99%